2018
DOI: 10.1177/2331216518785733
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Behavioral Evidence of Reduced Binaural Temporal Processing in the Aging and Hearing Impaired Human Auditory System

Abstract: A person’s ability to process temporal fine structure information is indispensable for speech understanding. As speech understanding typically deteriorates throughout adult life, this study aimed to disentangle age and hearing impairment (HI)-related changes in binaural temporal processing. This was achieved by examining neural and behavioral processing of interaural phase differences (IPDs). Neural IPD processing was studied electrophysiologically through steady-state activity in the electroencephalogram evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 65 publications
(114 reference statements)
3
18
0
Order By: Relevance
“…Similar to findings from studies that used different electrophysiological measurement techniques (Ross et al, 2007a;Ross, 2008;Ozmeral et al, 2016;Papesh et al, 2017;Ungan et al, 2020), Vercammen et al (2018) showed that the neural encoding of IPD cues tends to be stronger in younger participants compared to older participants and, along with several other studies (Haywood et al, 2015;Undurraga et al, 2016;Vercammen et al, 2018;Parthasarathy et al, 2020), showed that IPM-FR responses tend to be weaker when behavioral detection of the IPD cue is poor. While these previous studies have established that the IPM-FR is likely reflective of behavioral IPD sensitivity, the stimuli previously used to assess behavioral IPD discrimination thresholds were dichotic AM stimuli analogous to those used to elicit the IPM-FR (Haywood et al, 2015;Undurraga et al, 2016;Vercammen et al, 2018;Parthasarathy et al, 2020). Assessing relationships between the IPM-FR and other behavioral measures of binaural temporal processing will determine whether associations between the IPM-FR and behavior can generalize to other stimuli and tasks that assess IPD sensitivity.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…Similar to findings from studies that used different electrophysiological measurement techniques (Ross et al, 2007a;Ross, 2008;Ozmeral et al, 2016;Papesh et al, 2017;Ungan et al, 2020), Vercammen et al (2018) showed that the neural encoding of IPD cues tends to be stronger in younger participants compared to older participants and, along with several other studies (Haywood et al, 2015;Undurraga et al, 2016;Vercammen et al, 2018;Parthasarathy et al, 2020), showed that IPM-FR responses tend to be weaker when behavioral detection of the IPD cue is poor. While these previous studies have established that the IPM-FR is likely reflective of behavioral IPD sensitivity, the stimuli previously used to assess behavioral IPD discrimination thresholds were dichotic AM stimuli analogous to those used to elicit the IPM-FR (Haywood et al, 2015;Undurraga et al, 2016;Vercammen et al, 2018;Parthasarathy et al, 2020). Assessing relationships between the IPM-FR and other behavioral measures of binaural temporal processing will determine whether associations between the IPM-FR and behavior can generalize to other stimuli and tasks that assess IPD sensitivity.…”
Section: Introductionsupporting
confidence: 77%
“…This work aimed to (1) confirm previous findings that the IPM-FR, measures of binaural FM detection, and measures of spatial release from masking are sensitive to the effects of age on binaural temporal processing; (2) evaluate associations between the IPM-FR and performance on behavioral measures of IPD sensitivity and speech perception; and (3) explore differences in IPM-FRs elicited using different AM rates. It was predicted that, consistent with previous work (e.g., Grose and Mamo, 2012b;Gallun et al, 2013Gallun et al, , 2014Papesh et al, 2017;Vercammen et al, 2018;Ungan et al, 2020), age would have a significant effect on each neural and behavioral measure of binaural temporal processing, such that older participants would have reduced IPM-FRs, reduced dichotic FM thresholds, and reduced speech understanding abilities compared to younger participants. In addition, it was predicted that older participants would show reduced benefit from the addition of binaural cues in both the FM detection tasks and the spatial release-frommasking tasks compared to younger participants.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations